Unsur Modal Sosial Dalam Kelompok Tani Esa Tarendem Dan Kerknahel Di Kelurahan Rurukan Satu Kecamatan Tomohon Timur Kota Tomohon - Lontokan, Gisella Giovani; Kumaat, Ribka Magdalena; Maweikere, Audrey Julia Maria (Sam Ratulangi University, 2023)
This study aims to determine the element of social capital in farmer groups Esa Tarendem and Kerknahel in Rurukan Satu Village, East Tomohon District, Tomohon City. This research was conducted in Rurukan Satu Village, East Tomohon District, Tomohon City. This study began in April to June 2021, the number of samples used in this study amounted to twenty people. The types of data used in this study are primary data and secondary data. Primary data were obtained from direct interviews with farmer groups Esa Tarendem and Kerknahel using a list of questions (questionnaires), while secondary data was obtained from the Rurukan Satu sub-district government. The results of this study indicate that there is social capital in the Esa Tarendem farmer group in Rurukan Satu Village, East Tomohon District, Tomohon City. Where the results of the total score of 535 with a percentage of 99.07%. Meanwhile, the results of the research on social capital in the Kerknahel farmer group in Rurukan Satu Village, East Tomohon District, Tomohon City are doubtful. Where the results of the acquisition of a total score of 350 with a percentage of 64.81%.